The Vicissitudes of Positive Autobiographical Recollection as an Emotion Regulation Strategy in Depression. (January 2017) - Werner-Seidler, Aliza; Tan, Laura; Dalgleish, Tim
Recalling positive autobiographical memories is a powerful way to regulate emotion and repair low mood. However, depressed individuals often derive limited emotional benefit from such positive recollection. To identify the conditions under which positive memory recall is emotionally beneficial, we investigated whether memories perceived as discrepant from one's current sense of self have a differential impact on low mood compared to memories perceived as concordant with the current self. Depressed participants ( n = 39) recalled either a self-concordant or self-discrepant positive memory to alleviate sad mood and reported reduced sadness only when the memory was concordant with, but not discrepant from, their current sense of self. In contrast, never-depressed participants ( n = 40) experienced mood improvement regardless of the type of memory recalled. These results suggest that the degree to which depressed individuals can identify with the self from a past positive event is an important determinate of the emotional consequences that follow.